2015
DOI: 10.1021/acsami.5b01949
|View full text |Cite
|
Sign up to set email alerts
|

Multiscaling Approach for Non-Destructive Adhesion Studies of Metal/Polymer Composites

Abstract: The adhesion of polyamide 6 (PA6) and polyethylene (PE) toward an aluminum alloy (Al-A) and a dual phase steel (DPS) is studied by contact angle (CA) measurements and atomic force microscopy (AFM). With the combination of the two methods the adhesion properties on a macro- and (sub)microscopic scale can be determined in a nondestructive way. The work of adhesion per area (Wad) of the studied metal/polymer hybrids qualitatively scales the same on both length scales, that is, Al-A/PA6 > DPS/PA6 > Al-A/PE, DPS/PE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 53 publications
(82 reference statements)
0
14
0
Order By: Relevance
“…Recently, metal components used in the automotive, aerospace, and microelectronics industries are increasingly replaced by polymer and composite materials. At the same time, the importance of adhesives and adhesion technology has increased due to the diversity of used materials. This accelerating trend requires a new reliable technology, including surface modification methods for dissimilar materials bonding. In contrast to the intensive studies of epoxy monoliths as column fillers and separators for high-performance separation systems, we can find no report regarding the application of epoxy monolith for adhesion in the literature. Our preliminary results revealed that epoxy monolith was available for bonding of a stainless steel (SUS430) plate and thermoplastics. , In this study, we demonstrate the validity of the epoxy monolith bonding for dissimilar material bonding between various metals and polymers.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, metal components used in the automotive, aerospace, and microelectronics industries are increasingly replaced by polymer and composite materials. At the same time, the importance of adhesives and adhesion technology has increased due to the diversity of used materials. This accelerating trend requires a new reliable technology, including surface modification methods for dissimilar materials bonding. In contrast to the intensive studies of epoxy monoliths as column fillers and separators for high-performance separation systems, we can find no report regarding the application of epoxy monolith for adhesion in the literature. Our preliminary results revealed that epoxy monolith was available for bonding of a stainless steel (SUS430) plate and thermoplastics. , In this study, we demonstrate the validity of the epoxy monolith bonding for dissimilar material bonding between various metals and polymers.…”
Section: Introductionmentioning
confidence: 99%
“…During the mechanical deformation of flexible devices, the interfacial adhesion between rigid and soft materials with huge differences in moduli has always been considered as a crucial engineering problem, especially for mechanical interactions between different layers and rigid metal electrodes on elastic substrates. Conventional solutions to improve adhesion rely on the introduction of adhesion materials, such as a thin layer of metals (Cr, Ti) or a chemically activated layer on the surface. ,,, Inspired by natural creatures, structural modification at interfaces would constitute a valuable and effective solution to this problem. ,, For example, root systems show remarkable mechanical properties that enable plants survive in complex and hostile environments. Therefore, the structure of root systems can be introduced at interfaces between electrodes and soft substrates to realize desirable stretchability and high adhesion (Figure a).…”
Section: Structural Material-dominated Functionalization In Flexible ...mentioning
confidence: 94%
“…During the mechanical deformation of flexible devices, the interfacial adhesion between rigid and soft materials with huge differences in moduli has always been considered as a crucial engineering problem, especially for mechanical interactions between different layers and rigid metal electrodes on elastic substrates. [632][633][634][635][636][637][638][639] Conventional solutions to improve adhesion rely on the introduction of adhesion materials, such as a thin layer of metals or a chemically activated layer on the surface. 107,241,633,[640][641][642][643][644][645] Inspired by natural creatures, structural modification at interfaces would constitute a valuable and effective solution to this problem.…”
Section: Interfacial Interactions In Flexible Devicesmentioning
confidence: 99%
“…Surfaces in close contact observed under lower resolution frequently reveal gaps when inspected at the atomic length scale ( Figure 1 ). 13 15 Thus, the NSCA is usually lower (at maximum equal) than the contact observed at lower resolution. 16 18 In conclusion, direct observation of NSCA is only possible with imaging techniques having a resolution in the length scale of the interaction forces, i.e., around 1 nm.…”
Section: Introductionmentioning
confidence: 95%